NUMERICAL SIMULATION STUDIES ON THE PROCESS OF MACHINING OF SHAFTS WITH LOW RIGIDITY - Antoni ŚWIĆ; Arkadiusz GOLA (Applied Computer Science, 2016)
The paper presents a computer program developed for the determination of the basic dynamic characteristics of the process of machining, numerical simulations of the dynamic system of the process of machining, and graphic presentations of the numerical simulations performed. Results of simu-lations of the runs of time and frequency characteristics of the process of machining with variable machining parameters are presented. High goodness-of-fit of the model with the actual process of turning was achieved.